EFEK SEREI (CYMBPOGON CITRATUS) TERHADAP DIABETES T2: Insights from a Comprehensive Review of the Literature - Yuliana, Yuliana; M. Hutapea, Albert (Ensiklopedia of Journal, 2024)
Blood sugar levels increase after eating and decrease when you wake up in the morning. The presence of insulin in the body is very important to avoid diabetes. Reducing blood sugar levels is with complementary therapy, which can also be called complementary-alternative therapy. One of the complementary therapies that can be applied to Type II DM sufferers is the intake of Lemongrass extract (cymbpogon citratus). The Lemongrass plant (Cymbopogon citratus) is a herbal plant with chemical contents consisting of alkaloids, saponins, tannins, flavonoids, phenols, steroids which can act as antidiabetics. Research Objectives Determine the Effect of Lemongrass Extract Tea (Cymbpogon Citratus) on T2 Diabetes. Research method Literature review using databases via Proquest, Pubmed Central, Google Scholar with the results of 1,554 journals excluded because they were published in 2018 and above and used languages other than Indonesian and English, and research journals in Assessment then journals that were published and journals that were not in accordance with the inclusion and exclusion criteria, resulting in 6 journals that have been reviewed using inclusion and exclusion criteria in the PICOS format. Conclusion: Lemongrass tea compounds containing flavonoids and phenolic compounds have antidiabetic effects, improving glucose tolerance, beta cell function and dyslipidemia. Lemongrass as an anti-diabetic product contains flavonoid compounds and phenolic compounds which have anti-diabetic effects, improve glucose tolerance, beta cell function and dyslipidemia.Key words: complementary-alternative therapy, reducing sugar levels, glucose, lemongrass, Type II DM.